Looking at the Traces of Islamic Education in Saudia Arabia (Study of the History of Islamic Education) - Harahap, Muhammad Sapii (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
This research aims to find out the names of Islamic educational institutions, and to find out some of the names of educators and Islamic education figures. In this research the author uses historical methods or historical methods. The historical method consists of data collection, source criticism, interpretation and finally historiography. The research approaches used in this research are the geographical approach, sociological approach, educational approach and historical education. The results of this research are A) Saudi Arabia has 34 universities, with details of 26 state universities, namely: 1) Universitas Raja Saud, 2) Universitas Islam Madinah, 3) Universitas Raja Fahd untuk Perminyakan dan Mineral, 4) Universitas Raja Abdul Aziz, 5) Universitas Islam Imam Muhammad bin Saud, 6) Universitas Raja Faisal, 7) Universitas Umm Al-Qura, 8) Universitas Raja Khalid, 10) Universitas Qashim, 11) Universitas Taibah, 12) Universitas Ta'if, 13) Universitas Raja Saud bin Abdul Aziz untuk Ilmu Kesehatan, 14) Universitas Al-Bahah, 15) Universitas Ha'il, 16) Universitas Al-Jauf, 17) Universitas Jazan, 18) Universitas Najran, 19) Universitas Tabuk, 20) Universitas Putri Nurah binti Abdurrahman, 21) Universitas Al-Hudud Asy-Syamaliyyah, 22) Universitas Dammam, 23) Universitas Pangeran Salman bin Abdul Aziz, 24) Universitas Syaqra, 25) Universitas Al-Mujamma'ah, dan 26) Universitas Elektronik Saudi. dan 9 Perguruan Tinggi Swasta, yaitu: 1) Universitas Pangeran Sultan, 2) Universitas Terbuka Arab, 3) Universitas Internasional Al-Madinah, 4) Universitas Al-Yamamah, 5) Universitas Raja Abdullah untuk Sains dan Teknologi, 6) Universitas Al-Faisal, 7) Universitas Pangeran Muhammad bin Fahd, 8) Universitas Pangeran Fahd bin Sultan, dan 9) Universitas Darul 'Ulum. B) several figures and educators in Saudia Arabia are: 1) Ibn Taimiyyah Rahimahullah, 2) Muhammad Ibn Abd Al-Wahab Rahimahullah, 3) Abdul Aziz bin Shalih bin Nashir bin Abdurrahman Alu Shaikh rahimahullah, 4) Syaikh Abdul Aziz bin Abdullah bin Baz Rahimahullah, dan 5) Syaikh Muhammad bin Shalih al-Utsaimin Rahimahullah.